The role of communication of performance schemes: Evidence from a field experiment - Florian Englmaier; Andreas Roider; Uwe Sunde (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2015)
In corporate practice, incentive schemes are often complicated even for simple tasks. Hence, the way they are communicated might matter. In a controlled field experiment, we study a minimally invasive change in the communication of a well-established incentive scheme - a reminder regarding the piece rate at the beginning of the shift. The experiment was conducted in a large firm where experienced managers work in a team production setting and where incentives for both quantity and quality of output are provided. While the treatment conveyed no additional material information and left the incentive system unchanged, it had significant positive effects on quantity and on managers' compensation. These effects are economically sizable and robust to alternative empirical specifications. We consider various potential mechanisms, where our preferred explanation - improved salience of incentives - is consistent with all of the findings.
Keywords: M52; J30; D03; D80; 330; incentives; attention; salience; communication; field experiment